Epstein–Barr Virus-Induced Metabolic Rearrangements in Human B-Cell Lymphomas - Piccaluga, Pier P.; Weber, Alessandra; Ambrosio, Maria R.; Ahmed, Yonis; Leoncini, Lorenzo (Frontiers in Microbiology, 2018)
Tumor metabolism has been the object of several studies in the past, leading to the pivotal observation of a consistent shift toward aerobic glycolysis (so called Warburg effect). More recently, several additional investigations proved that tumor metabolism is profoundly affected during tumorigenesis, including glucose, lipid and amino-acid metabolism. Of note, metabolic reprogramming can represent a suitable therapeutic target in many cancer types. Epstein-Barr virus (EBV) was the first virus linked with cancer in humans when Burkitt lymphoma (BL) was described. Beside other well-known effects, it was recently demonstrated that EBV can induce significant modification in cell metabolism that may lead or contribute to neoplastic transformation of human cells. Similarly, more in general, virus-induced tumorigenesis is characterized by relevant metabolic abnormalities directly induced by the oncoviruses. In this article the Authors critically review the most recent literature concerning EBV-induced metabolism alterations in lymphomas.